DISCLOSURE OF AUTHORITY OF THE CORRUPTION ERADICATION COMMISSION (KPK) IN THE POST LAW CHANGE CORRUPTION ERADICATION COMMISSION - Ricky Pratama Ginting; Sumarno (Universitas Efarina, 2023)
After the passing of the Corruption Eradication Commission (KPK) Law, the position of the KPK, which was originally a non-governmental institution, is now included in the branch of government power (Auxiliary State Organ). The only corruption eradication institution (excluding the Police and Prosecutor's Office) that still survives to this day is the Corruption Eradication Commission, namely the independent commission which is given pro justitia authority in carrying out criminal acts of corruption. So far this has not been without criticism. In carrying out its duties and functions (before the revision of the Law), many experts criticized the institution for its